2008
DOI: 10.1149/1.3050390
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Titanate-based Composite Anodes for Solid Oxide Fuel Cells

Abstract: Surfactant-assisted infiltration of Gd-doped ceria (CGO) in Nb-doped SrTiO3 (STN) was investigated as a potential fuel electrode for solid oxide fuel cells (SOFC). An electronically conductive backbone structure of STN was first fabricated at high temperatures and then combined with the mixed conducting and electrochemically active nano-sized CGO phase at low temperatures. Symmetrical cell measurements at open circuit voltage (OCV), showed that the electrochemical activity was maintained or even improved compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
(35 reference statements)
3
27
0
Order By: Relevance
“…Symmetrical cells were prepared with electrodes comprised of porous Sr 0.94 Ti 0.9 Nb 0.1 O 3 (STN) backbones coated with Ce 0.8 Gd 0.2 O 1.9 by surfactantassisted nitrate solution inltration, on both sides of a YSZ electrolyte, as described in ref. 33. Pt paste was applied to both electrodes for current collection.…”
Section: Methodsmentioning
confidence: 99%
“…Symmetrical cells were prepared with electrodes comprised of porous Sr 0.94 Ti 0.9 Nb 0.1 O 3 (STN) backbones coated with Ce 0.8 Gd 0.2 O 1.9 by surfactantassisted nitrate solution inltration, on both sides of a YSZ electrolyte, as described in ref. 33. Pt paste was applied to both electrodes for current collection.…”
Section: Methodsmentioning
confidence: 99%
“…(14). Table I shows the different compounds that were investigated by infiltration in symmetrical cells.…”
Section: Catalyst Infiltrationmentioning
confidence: 99%
“…It was shown that the electrochemical activity was maintained or even improved compared to Ni/YSZ fuel electrodes. The electrocatalytic activity and oxygen ECS Transactions, 25 (2) 701-710 (2009) ion transport was believed to be provided by the CGO nano-particle network covering the STN backbone structure whereas the STN backbone structure mainly provided electronic conductivity (14).…”
Section: Introductionmentioning
confidence: 99%
“…Nb-doped SrTiO 3 has been shown to have high electronic conductivity and promising redox stability (5,6). Combined with infiltration of electrocatalytically active materials the performance of such an anode has been shown to be comparable to conventional Ni-YSZ based anodes (7). In general, various perovskite structured materials as fuel cell anodes have, since a few years back, been proposed as promising candidates for the future (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%